Logistical and financial obstacles for endovascular therapy of acute stroke implementation - Schellinger, Peter D.; Köhrmann, Martin; Nogueira, Raul G. (International Journal of Stroke, 2016)
After publication of the recent positive randomized clinical endovascular trials, several questions and obstacles for wide spread implementation remain. We address specific issues namely efficacy, safety, logistics, timing, sedation, numbers, imaging, manpower, centers, geographics, and economical aspects of endovascular therapy. As we move forward, a high degree of collaboration will be crucial to implement a therapy with established overwhelming treatment efficacy for severe acute stroke patients.
EVALuna2:22456